INFORMATION COMMUNICATION DEPLOYMENT IN TERTIARY EDUCATION - Ayoko, Victor Olugbenga (Multi-Disciplinary Research and Development Journals Int'l, 2025)
The integration of Information and Communication Technologies (ICTs) in tertiary education has transformed teaching, research, administration, and community service, making it a vital component of 21st-century higher education. ICT facilitates access to vast learning resources, enhances collaboration, and streamlines institutional processes. This chapter explores the deployment of ICT in Nigerian tertiary institutions, with emphasis on its application in teaching, research, and community service. The chapter begins with a clarification of key concepts, including tertiary education and ICT, and proceeds to highlight the imperative of ICT integration in higher education. The discussion underscores how ICT has enhanced teaching effectiveness, supported innovative pedagogical practices, and enabled inclusive learning for students with diverse needs. It also examines the role of ICT in advancing research through digital databases, virtual collaboration, and knowledge sharing. Furthermore, the chapter addresses the use of ICT in community service, where it improves project management, outreach, and data analysis for sustainable community development. Finally, the advantages of ICT integration—such as improved digital literacy, enhanced collaboration, cost reduction, and workforce readiness—are presented. The chapter concludes that ICT is indispensable for achieving the goals of tertiary education in Nigeria and globally. Its sustained integration into higher education curricula is essential for equipping graduates with the skills needed for the digital economy and for promoting national development.